Picking a (Poor) Partner: A Relational Perspective on Acquisitions. (June 2014) - Rogan, Michelle; Sorenson, Olav
Using comprehensive data from the global advertising industry from 1995 to 2003, we examined the effects of indirect ties (common clients) on acquirers' choices of partners for mergers and acquisitions and on the performance of the combined organizations. We found that the probability of being acquired rose but the performance of merged entities declined—both by losing clients and by selling less to the clients retained—with the number of common clients connecting the target to the acquirer. Two potential mechanisms could account for this pattern of results: either managers hold positively biased beliefs about those connected to them through common clients, or they restrict their searches for potential acquisition partners to those they already know, despite the disadvantages of doing so, ignoring targets that may have more potential but with whom they have no indirect ties.